Subjective Well-Being, Religiosity, Trust, and Altruism: an Islamic Perspective - Rakhmawati, Rakhmawati; Atmaja, Fajar Fandi (EKONOMIKA SYARIAH : Journal of Economic Studies, 2024)
Subjective well-being (SWB) is often associated with increased productivity, creativity, innovation, and improved social relationships, all of which play a significant role in supporting a country's development. This research was carried out to examine SWB from an Islamic perspective. It also evaluated the importance of religiosity, trust, and altruism to SWB. The library research method was used in this research with data collected from journal articles, books, and the Qur’an. First, journal articles on the topic of SWB from an Islamic perspective were searched. Second, the Qur’an was examined to determine the references to the roles of religiosity, trust, and altruism. Third, the publications on the impact of religiosity, trust, and altruism were reviewed. The topic of SWB, from an Islamic perspective, is associated with happiness, as represented by the terms al-falah and al sa’adah. The implications are for individuals, educators, families, and governments to increase SWB through the enhancement of important indicators. The research strengthens empirical evidence on the positive impact of religiosity, trust, and altruism on SWB. It also proved that Islamic teachings on muamalat (social relations) are universal and provided benefits to non-Muslims. Individu dengan kesejahteraan subjektif (subjective well-being/SWB) yang baik akan lebih produktif, kreatif, inovatif, dan memiliki hubungan sosial yang baik. Hal tersebut merupakan aspek penting dalam pembangunan suatu negara. Penelitian ini bertujuan untuk menganalisis SWB dari perspektif Islam serta bagaimana peran religiositas, kepercayaan, dan altruisme terhadap SWB. Penelitian ini menggunakan metode studi kepustakaan dengan data berasal dari artikel jurnal, buku, dan al-Qur’an. Pertama, artikel jurnal dengan topik SWB dalam perspektif Islam dibahas. Kedua, peran religiositas, kepercayaan dan altruisme dicari di dalam al-Qur’an. Ketiga, artikel jurnal terkait bukti empiris ketiga variabel tersebut terhadap SWB juga dibahas. Topik tentang SWB dalam perspektif Islam dihubungkan dengan kebahagiaan khususnya dengan istilah al-sa’adah dan al-falah. Implikasi dari penelitian ini adalah untuk individu, pendidik, keluarga, dan pemerintah untuk meningkatkan SWB melalui tiga variabel yang dibahas di sini. Penelitian ini menguatkan penelitian empiris bahwa ada peran positif dari religiositas, kepercayaan terhadap orang lain, dan sifat altruisme dalam meningkatkan kebahagiaan. Penelitian ini juga memberikan bukti bahwa ajaran Islam dalam muamalat (hubungan sosial) bersifat universal dan memberikan manfaat pada manusia bahkan untuk yang tidak beragama Islam.